Evaluation of catalase activity, gill histology and genotoxic effects of cadmium in tilapia (Oreochromis niloticus) fingerlings - Marium, Amna; Naz, Huma; Ahmed, Tanveer; Ijaz, Muhammad Umar; Usman, Muhammad; Manzoor, Zahid; Ali, Basharat; Omran, Awatif; Alanazi, Yasmene F.; Jame, Rasha M.A.; El Sabagh, Ayman (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research was designed to assess the toxicity of cadmium (Cd), and its effects on catalase (CAT) activity, histology of gills and geno-toxicity of Oreochromis niloticus. The acute toxicity of Cd (96-h) for fish was computed as 56.021 mg/L (LC50) and 80.7336 mg/L (LC100) using Probit method. The inferences showed that catalase level was significantly (P<0.05) lower in Cd treated O. niloticus as compared to control that was metal-stress free. It followed the order as: intestine<gills<muscles<brain. Results of gills histology showed that Cd-exposure caused prominent damage to both primary and secondary lamella. The histological alterations included fusion and curling of secondary lamella, hyperplasia in secondary lamella, epithelial lifting, and aneurysm observed in gills. Geno-toxic results showed that a significant (p<0.05) increase in micronuclei, de-shape and notched nuclei in erythrocytes of Cd-exposed O. niloticus was found as compared to control. The inferences of this study confirmed the genotoxic properties of Cd. This study will be helpful in understanding the histological and geno-toxic changes in fish body kept under Cd stress. This study will also help in the development of a specific approach to minimize the negative and genotoxic impacts of cadmium. Furthermore, tilapia can be used as a good bio-indicator for detecting toxic impacts associated with water pollution.